Clinical use of mineral trioxide aggregate (MTA) in periapical lesions and the treatment of root perforations - Pineda Mejía, Martha Elena (2007)
The use of MTA cement (mineral trioxide aggregate) to solve endodontics treatment complications, like pulpar floor camera perforations during root canal treatment, as well as a retrograde obturation material of apicectomy treatment, was the purpose of this investigation. White MTA Angelus, (Industria de productos odontologicos Ltda. Londrina-PR-Brazil) was used wich has 10 – 15 minutes as initial and final hardening time. The radiopacity showed by the material was somewhat superior to that of the dentine and oseo tissues, making its visualization in control x-rays easier. Inmediate and sixty days postoperative radiographic and clinical controls were made to cases. The results showed that there was adaptation from the cement to the retroapical and perforation cavity walls, producing an apical and marginal seal. The tricalcic silicate, tricalcic aluminate, dicalcic silicate, and tetracalcic ferric aluminate were the cement constituent elements; these allowed a stimulation of scaring and repair of the surrounding tissues that evolved in a favorable form until the moment of the last control was carried out in this investigation.